INVESTIGATION OF THE DIGITAL PODCAST TO DEVELOP STORYTELLING METHOD IN ISLAMIC SCHOOL DURING PANDEMIC DISRUPTION - Eka Selvi Handayani; Ismail Ismail; Mohamad Suhaidi; Tauhid Tauhid (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2020)
This paper suggested integrating podcast application to improve Islamic education storytelling sessions during pandemic COVID-19 disruption in Indonesia. The findings of a study about learning in schools and madrasahs believe that learning during a pandemic disturbance can be overcome with a remote learning system with the help of learning media with various digital applications. For this reason, we have reviewed various literature and online-based learning applications and scientific publications of the latest findings on how to deal with learning disabilities during COVID-19 to deepen new understanding to prove the assumption that many learning applications can help students learn during temporary shelters but open classrooms at a long distance. With the evidence of existing studies from various literature and scientific publications on online learning and pandemic disruption, we can say that the effectiveness of integrating the Podcast application has become an alternative superiority of distance learning media among students in Islamic boarding schools in Indonesia. Therefore, we highly recommend pesantren's academics, especially students in the Islamic education environment, and teachers outside the Islamic boarding school to integrate digital media podcasts as an alternative distance learning solution during disruption and the new normal learning period because of the advantages and effectiveness of podcasts application for learning in Indonesia.